2018
DOI: 10.1038/s41598-018-19820-1
|View full text |Cite
|
Sign up to set email alerts
|

Inferences on specificity recognition at the Malus×domestica gametophytic self-incompatibility system

Abstract: In Malus × domestica (Rosaceae) the product of each SFBB gene (the pollen component of the gametophytic self-incompatibility (GSI) system) of a S-haplotype (the combination of pistil and pollen genes that are linked) interacts with a sub-set of non-self S-RNases (the pistil component), but not with the self S-RNase. To understand how the Malus GSI system works, we identified 24 SFBB genes expressed in anthers, and determined their gene sequence in nine M. domestica cultivars. Expression of these SFBBs was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 87 publications
1
27
0
1
Order By: Relevance
“…Here, Fragaria vesca, Fragaria × ananassa, and Malus × domestica (only these three species in the present study can be found the available RNA-seq data to analyze the expression profiles about diverse tissues and stresses) were considered when investigating the RALF-like gene expression of diverse tissues, organs, developmental stages, and stresses. The study accessions from NCBI were SRP096282, SRP098567, ERP004230, SRP035308, SRP018410, ERP013896, SRP111905, SRP125281, SRP091754, and SRP139480 [54][55][56][57][58][59][60][61], which were involved in the development of flower tissues, fruit tissues, seed tissues, and fungal stresses. Ultimately, the FPKM (fragments per kilobase per million) [62] of RALF-like genes was extracted from the GTF files and submitted to TBtools [52] to draw the heatmaps with the log 2 translation of FPKM.…”
Section: The Expression Profiles Of Ralf-like Genes In Strawberry Andmentioning
confidence: 99%
“…Here, Fragaria vesca, Fragaria × ananassa, and Malus × domestica (only these three species in the present study can be found the available RNA-seq data to analyze the expression profiles about diverse tissues and stresses) were considered when investigating the RALF-like gene expression of diverse tissues, organs, developmental stages, and stresses. The study accessions from NCBI were SRP096282, SRP098567, ERP004230, SRP035308, SRP018410, ERP013896, SRP111905, SRP125281, SRP091754, and SRP139480 [54][55][56][57][58][59][60][61], which were involved in the development of flower tissues, fruit tissues, seed tissues, and fungal stresses. Ultimately, the FPKM (fragments per kilobase per million) [62] of RALF-like genes was extracted from the GTF files and submitted to TBtools [52] to draw the heatmaps with the log 2 translation of FPKM.…”
Section: The Expression Profiles Of Ralf-like Genes In Strawberry Andmentioning
confidence: 99%
“…As yet, it is still unclear how many SFBB genes are involved in the GSI system. However, based on findings in apple ( Malus domestica ), the currently estimated number of SFBB genes is 17–19 (Pratas et al., 2018). In addition, the S-locus sequence in pear was also found to contain numerous transposon-like sequences which are proposed to generate polymorphisms among S-haplotypes, and which likely contribute to the suppression of meiotic recombination between the S-RNase and SFBBs (Okada et al., 2011).…”
Section: The Genetic Control Of Gsi In Pyrusmentioning
confidence: 99%
“…In M. domestica , 10 S-haplotypes were screened for the presence of SFBB genes using transcriptome sequencing of anthers. For a given S-haplotype, this resulted in the identification of 17–19 SFBB genes (Pratas et al., 2018). A similar number of SLF genes (namely 16–20 SLF genes, classified into 18 types) was observed in Petunia , which also exhibits a non-self-recognition type GSI system (Matsumoto and Tao, 2016a; Pratas et al., 2018).…”
Section: The Genetic Control Of Gsi In Pyrusmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-seq analysis has emerged as the preferred technique for transcriptome studies (Wang et al, 2009) and it has played an important role in elucidating the non-self recognition GSI system in Solanaceae and Rosaceae. It was used in Petunia to identify all the pollen specificity SLF genes (Williams et al, 2014;Kubo et al, 2015 ), and up to 24 S-locus Fbox Brothers (SFBB) genes were similarly identified in Malus × domestica (Pratas et al, 2018).…”
Section: Future Prospectsmentioning
confidence: 99%